Rwanda Economic Update, June 2015 : Financing Development - World Bank Group (World Bank, Washington, DC, 2015)
Growth recovery in 2014 is certainly good news. This time last year, we estimated the 2014 growth rate at 5.7 percent. Against all odds, the economy grew by 7 percent. However,growth outlook is not entirely bright. While the oil price decline has brought a positive impact oninflation and trade, recent economic indicators show some weaknesses. Also, global risks (e.g.,an increase in US interest rate, slowdown of Chinese and Euro economies, and an appreciationof the US dollar) are emerging. In the medium to long-term, Rwanda’s economic resiliencewill not be achieved without keeping high investment rates. However, the current investmentmodel (high public investment funded by aid) is not likely to be sustainable; given capacityconstraints to maintain high public investment and possible decline in aid relative to GDP inthe medium-term. Finding alternative sources of development financing is a key determinantof future growth. Development of the financial sector is critical to mobilize both domestic andforeign saving for financing development. This is the message of the Eighth Edition of theRwanda Economic Update (REU).